Research on the Measurement of Carbon Storage in Plantation Tree Trunks Based on the Carbon Storage Dynamic Analysis Method - Weida Yin; Mingfang Yin; Lin Zhao; Lin Yang (International Journal of Forestry Research)
Estimation of forest carbon storage can be of great significance to the research on the productivity of terrestrial ecosystem, carbon cycle, and global warming. China has more than 54 million hm2 barren hills and waste land suitable for forestation, which provides a great potential for developing carbon sink forestry by means of forestation. This research analyzed the volume increments, volume densities, and carbon contents of 15 analytical samples of five main plantation tree species in North China, including Pinus tabulaeformis (A), Robinia pseudoacacia (B), Populus euramericana (C), Larix olgenisis (D), and Larix kaempferi (E). Results showed that carbon storage dynamic process can be expressed as follows: the ages of quantitative maturity of each tree species are 67a, 40a, 30a, 48a, 49a, respectively; the average wood densities of each tree species at different age classes are 550.93 kg/m3, 629.25 kg/m3, 404.56 kg/m3, 592.33 kg/m3, and 544.11 kg/m3,t. The average carbon contents of each tree species at different age classes are 51.48%, 46.88%, 47.81%, 46.76%, and 47.24%. It showed a significant difference between the above tree species through variance test. The maximum values of average carbon storage are 70a, 40a, 30a, 48.7a, and 49.2a, respectively. The corresponding average carbon storages are A 2.527 kg, B 3,794 kg, C 2.781 kg, D 2.996 kg, and E 3,322 kg, in a descending order of C>E>D>B>A. This research, through experiment on four tree species with clear growth rings and one tree species with unclear growth rings, verified the scientific character and the scope of application of the carbon storage dynamic analysis method, providing a new method for the measurement and analysis of forest carbon storage.